Analisis Kinerja Waktu Dan Biaya Pada Proyek Pembangunan Gedung Labkesda Ende Menggunakan Metode Earned Value - Maximus Raja; Yohanes Laka Suku; Veronika Miana Radja (TEKNOSIAR, 2026)
ABSTRACT The construction project of the Regional Health Laboratory Building (LABKESDA) in Ende requires effective time and cost control to ensure that project implementation runs according to the planned schedule and budget. During its implementation, discrepancies occurred between the planned schedule and the actual progress in the field, resulting in project delays. This study aims to analyze the time and cost performance of the LABKESDA Ende building construction project using the Earned Value method. The analysis was conducted through the indicators of Budgeted Cost of Work Scheduled (BCWS), Budgeted Cost of Work Performed (BCWP), Actual Cost of Work Performed (ACWP), Cost Variance (CV), Schedule Variance (SV), Cost Performance Index (CPI), and Schedule Performance Index (SPI). The research method used was descriptive quantitative analysis using project weekly reports, time schedules, and project budget plans (RAB) as research data. The data were analyzed using the Earned Value concept to determine the efficiency level of project cost and time performance. The results showed that the BCWP value was lower than BCWS, indicating that the project experienced implementation delays. Negative SV values and SPI values below 1 indicate that the project time performance did not meet the planned schedule. Meanwhile, CPI values close to or greater than 1 indicate that project costs were still relatively efficient and under control. Project delays were influenced by several factors, including delays in material procurement, weather conditions, changes in field work, limited labor resources, and weak project control. Based on the results of the study, the Earned Value method proved capable of providing quantitative and comprehensive information regarding the actual project condition and can therefore be used as a basis for decision-making in construction project time and cost control. Keywords: project performance, time and cost control, Earned Value, BCWS, BCWP, ACWP. ABSTRAK Proyek pembangunan Gedung Laboratorium Kesehatan Daerah (LABKESDA) Ende merupakan salah satu proyek konstruksi yang memerlukan pengendalian waktu dan biaya secara efektif agar pelaksanaannya berjalan sesuai dengan rencana. Dalam pelaksanaannya, proyek mengalami ketidaksesuaian antara jadwal rencana dan realisasi pekerjaan di lapangan yang berdampak pada keterlambatan pelaksanaan proyek. Penelitian ini bertujuan untuk menganalisis kinerja waktu dan biaya pada proyek pembangunan Gedung LABKESDA Ende menggunakan metode Earned Value. Analisis dilakukan melalui indikator Budgeted Cost of Work Scheduled (BCWS), Budgeted Cost of Work Performed (BCWP), Actual Cost of Work Performed (ACWP), Cost Variance (CV), Schedule Variance (SV), Cost Performance Index (CPI), dan Schedule Performance Index (SPI). Metode penelitian yang digunakan adalah deskriptif kuantitatif dengan menggunakan data berupa laporan mingguan proyek, time schedule, dan Rencana Anggaran Biaya (RAB). Data dianalisis menggunakan konsep Earned Value untuk mengetahui tingkat efisiensi biaya dan waktu pelaksanaan proyek. Hasil penelitian menunjukkan bahwa nilai BCWP lebih kecil dibandingkan BCWS, yang mengindikasikan bahwa proyek mengalami keterlambatan pelaksanaan. Nilai SV yang bernilai negatif dan nilai SPI yang berada di bawah 1 menunjukkan bahwa kinerja waktu proyek belum sesuai dengan jadwal rencana. Sementara itu, nilai CPI yang mendekati atau lebih besar dari 1 menunjukkan bahwa penggunaan biaya proyek masih berada dalam kondisi yang relatif efisien dan terkendali. Keterlambatan proyek dipengaruhi oleh beberapa faktor, antara lain keterlambatan pengadaan material, kondisi cuaca, perubahan pekerjaan di lapangan, keterbatasan tenaga kerja, serta lemahnya pengendalian proyek. Berdasarkan hasil penelitian, metode Earned Value terbukti mampu memberikan gambaran kondisi aktual proyek secara kuantitatif dan komprehensif sehingga dapat digunakan sebagai dasar pengambilan keputusan dalam pengendalian waktu dan biaya proyek konstruksi. Kata kunci: kinerja proyek, pengendalian waktu dan biaya, Earned Value, BCWS, BCWP, ACWP.